SIDE: An Application-Based Happy Spiritual Intervention For Emotion Regulation Among Nursing Students During Online Learning - Meidiana Dwidiyanti; Badrul Munif; Fitria Handayani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Problems and uncertainty during online learning often cause negative emotions among nursing students, such as anxiety, anger, stress, and confusion. A comprehensive treatment is needed to help students cope with uncertain situations. One strategy that can be implemented is to regulate emotions using the Emotion Detection Information System (SIDE) application. SIDE contains some features of emotion detection and happy spiritual intervention for regulating emotions. Objective: This study aimed to determine the effect of the SIDE application on emotion regulation among nursing students. Methods: This research was a quantitative study with a one-group pretest-posttest design without a control group. This study described its data in one group before and after the intervention using a modified Emotional Regulation Questionnaire (ERQ). This study was conducted among 46 nursing students. Results: The paired sample t-test showed a significance level of 0.000 (p less than 0.005), indicating a significant effect of the SIDE application on the emotional regulation ability of nursing students. Conclusion: The SIDE application had a positive effect on emotional regulation among nursing students. The students had better emotional regulation abilities so that they could minimize the symptoms of mental disorders while facing uncertainty during the COVID-19 pandemic. Abstrak: Latar belakang: Problematika dan ketidakpastian selama pembelajaran daring seringkali menimbulkan emosi negatif seperti kecemasan, marah, stres, dan bingung pada mahasiswa keperawatan. Penanganan yang komprehensif diperlukan untuk membantu mahasiswa mengatasi situasi-situasi yang tidak menentu. Salah satu cara yang dapat dilakukan adalah pengaturan regulasi emosi dengan bantuan aplikasi Sistem Informasi Deteksi Emosi (SIDE). SIDE berisi beberapa fitur deteksi emosi serta intervensi happy spiritual dalam regulasi emosi. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan aplikasi SIDE terhadap regulasi emosi pada mahasiswa keperawatan. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain one group pretest-posttest without control. Dimana penelitian ini menggambarkan data pada satu kelompok sebelum dan sesudah diberikan intervensi dengan mengunakan alat ukur berupa kuesioner modifikasi The Emotional Regulation Questionnaire (ERQ). Hasil: Penelitian yang dilakukan kepada 46 mahasiswa keperawatan menunjukkan hasil uji paired sample t-test dengan nilai sig. 0,000 (p kurang dari 0,005). Hal ini menunjukkan adanya pengaruh yang signifikan dari penerapan aplikasi SIDE pada kemampuan regulasi emosi mahasiswa keperawatan. Kesimpulan: Penerapan aplikasi SIDE terhadap regulasi emosi mahasiswa keperawatan menunjukkan hasil adanya pengaruh yang positif, dimana mahasiswa keperawatan memiliki kemampuan regulasi emosi yang lebih baik sehingga dapat meminimalkan gejala gangguan mental selama menghadapi ketidakpastian di masa pandemi COVID-19.